Cell-Based Seafood Production: Part 3—Regulatory Framework in the United States and Food Safety Considerations: FSHN24-1/FS456, 8/2024 - Omidvar, Rose; Farzad, Razieh (EDIS, 2024)
In this EDIS publication, we provide information on the current regulatory framework for cell-based seafood production in the United States, food safety considerations, and the path forward for cell-based seafood products to get approved for selling in the marketplace. Additionally, drawing on the available science-based risk analysis methods for seafood production such as Hazards Analysis Critical Control Point (HACCP), we provided a simple hazard analysis to identify the potential seafood hazards that can potentially compromise the safety of cell-based seafood products.